Bing-Neel syndrome – Bilateral cavernous sinus lymphoma causing visual failure. (November 2017) - Pham, Chengde; Griffiths, James D.; Kam, Anthony; Hunn, Martin K.
Highlights: Bing-Neel syndrome, Waldenstrom macroglobulinaemia with central nervous system (CNS) involvement, is extremely rare. This is the first documented case of Bing-Neel syndrome with bilateral cavernous sinus involvement causing visual failure. As lymphoma treatment improves, CNS recurrence must be considered in the differential for new neurological symptoms. Vision loss in elderly patients is not always due to cataract. Abstract: We report the case of a 68-year-old male with right eye vision loss secondary to a compressive optic neuropathy from Waldenstrom macroglobulinaemia relapse in both cavernous sinuses. Central nervous system involvement is extremely uncommon in lymphoplasmacytic lymphoma. Known as Bing-Neel syndrome, this has not been previously reported to present simultaneously in bilateral cavernous sinuses. We discuss the pathophysiology, diagnostic and neuroradiological features of Bing-Neel syndrome. In this case, there was marked clinical and radiological response to chemotherapy. As outcomes following treatment for Waldenstrom macroglobulinaemia improve, greater awareness of its less common manifestations becomes important. Neurosurgical intervention may be indicated to obtain histological diagnosis or decompress critical structures.